Cultural Specific Items on Tourism Menu in The Cirebon City Government Official Website (Indonesian Version) - Nur Fadilah Kurnia; Eva Utami Durahman; Fedro Iswandi (Syntax Literate, 2022)
The purpose of this research is to classify the category of Cirebon cultural specific items category that found on the tourism menu on the website www.cirebonkota.go.id. This research is a qualitative descriptive method. This research used the theory of cultural specific items proposed by Pavlovic & Poslek (2003). Data collection techniques are interviews and document analysis. The findings of this study show that there are 144 data on Cirebon cultural specific items which are divided into 11 categories, including ecology (5 data), everyday life (31 data), material culture (10 data), religion (17 data), history (47 data), education (1 data), the armed forces (2 data), political and administrative functions and institutions (3 data), forms of address (9 data), work (1 data), and leisure & entertainment (18 data). Based on these results, history is the most frequently appearing category of the cultural specific item on the website. This indicates that history is necessary to learn in order to grasp historical differences and learn to be tolerant.